Preventive Behaviors and Knowledge of Tick-Borne Illnesses: Results of a Survey From an Endemic Area. (May 2015) - Valente, Sara L.; Wemple, Daniel; Ramos, Sebastian; Cashman, Suzanne B.; Savageau, Judith A.
Abstract : Context: Lyme disease (LD) is the most commonly reported vector-borne illness in the United States. With physically and economically burdensome effects, it is a concern of public health officials. Objectives: To assess knowledge and preventive behaviors of individuals in the endemic area of Martha's Vineyard, Massachusetts, to better understand how sociodemographic data and knowledge correlate with preventive behaviors, and to update previous island studies. Design: A 30-item paper-based anonymous survey in either English or Portuguese based on language preference. Setting: The island of Martha's Vineyard and the ferry between island and mainland. Participants: A total of 946 participants were recruited at 1 of 4 island locations. The majority of participants were traveling by ferry to and from Martha's Vineyard. To reach 2 populations potentially at high risk, that is, youths and outdoor workers, 3 additional venues included the island high school, an English-as-a-Second-Language class, and a local Brazilian church. Outcome Measures: Four specific preventive behaviors as well as an overall composite prevention score. Results: Participants' knowledge of tick-borne illnesses was poor, and the frequency of practicing preventive behaviors was low; the most commonly reported behavior was checking one's skin for ticks (45%). Approximately one-third of respondents (37%) stated that they did not know the late symptoms of untreated LD, nor did they know early LD treatment options (49%). The 2 high-risk groups reported little participation in preventive measures. In multivariate analyses, only 4 characteristics—older age, confidence in telling deer tick from wood tick, seeing tick-borne illness as a serious threat, and certainty in ability to identify LD symptoms—attained significance associated with preventive behavior as an overall composite score. Conclusions: Public health interventions focusing on accurately communicating risk, improving knowledge both of LD symptoms and of ticks that carry the disease, as well as teaching preventive behaviors may help reduce tick-borne illness rates. Abstract : Supplemental Digital Content is Available in the Text.This article provides results of a survey to assess knowledge and preventive behaviors of individuals in the Lyme disease endemic area, to better understand how sociodemographic data and knowledge correlate with preventive behaviors, and to update previous island studies.